Effective approaches for managing electronic records and archives - Dearstyne, Bruce W. ed. (Scarecrow P. LanhamUS, 2002)
Includes fresh insights, perspectives, strategies and approaches for managing electronic records, particularly those of enduring value, and for strengthening the operation of archival programs in digital environments.